Control interno presupuestario del GAD municipal del Cantón Vinces, en el período 2022 - León Zamora, Josmar Meredid (2023)
This study focuses on evaluating the budgetary internal control of the Municipal Decentralized Autonomous Government (GAD) of the Vinces Canton during the year 2022. The identified problem is related to deficiencies in budget management, which can affect the efficiency and transparency of financial processes. The justification lies in the importance of ensuring proper financial management in government entities for the efficient use of public resources. The general objective is to determine the state of budgetary internal control in the Vinces GAD and evaluate its financial processes. The methodology included the review of financial records, an internal control matrix, and interviews with financial personnel. In conclusion, deficiencies in budget management were identified, such as the lack of documentation and periodic review of financial reports. The importance of establishing clear processes, spending limits, personnel training, and leadership commitment to improve financial internal control in the Vinces GAD was highlighted.